What keeps health professionals working in rural district hospitals in South Africa? - Louis S. Jenkins; Colette Gunst; Julia Blitz; Johan F. Coetzee (AOSIS, 2015)
Background: The theme of the 2014 Southern African Rural Health Conference was 'Building resilience in facing rural realities'. Retaining health professionals in South Africa is critical for sustainable health services. Only 12% of doctors and 19% of nurses have been retained in the rural areas. The aim of the workshop was to understand from health practitioners why they continued working in their rural settings. Conference workshop: The workshop consisted of 29 doctors, managers, academic family physicians, nurses and clinical associates from Southern Africa, with work experience from three weeks to 13 years, often in deep rural districts. Using the nominal group technique, the following question was explored, 'What is it that keeps you going to work every day?' Participants reflected on their work situation and listed and rated the important reasons for continuing to work. Results: Five main themes emerged. A shared purpose, emanating from a deep sense of meaning, was the strongest reason for staying and working in a rural setting. Working in a team was second most important, with teamwork being related to attitudes and relationships, support from visiting specialists and opportunities to implement individual clinical skills. A culture of support was third, followed by opportunities for growth and continuing professional development, including teaching by outreaching specialists. The fifth theme was a healthy work-life balance. Conclusion: Health practitioners continue to work in rural settings for often deeper reasons relating to a sense of meaning, being part of a team that closely relate to each other and feeling supported.